The impact of cementing technique in polished taper fit hip stems: a modelling analysis of implant-cement interface - Bernard H. van Duren; Mohamad Taufiqurrakhman; Alison Jones; Mark Higgins; Andrew R. Manktelow; Benjamin V. Bloch; Hemant Pandit (Bone & Joint Research)
Aims: Cemented polished taper fit (PTF) stems are the femoral implant of choice for total hip arthroplasty (THA) in many locations worldwide. There is increasing evidence that periprosthetic fracture may be the single major contributor to reoperation with these stems. The aim of this study was to demonstrate how mismatches at the implant-cement interface may occur and the subsequent effect of these incongruities on the contacting area and the forces transmitted to the cement mantle. Methods: A parametric equation-based model was developed to determine the contact mismatch relative to axial stem rotations. This model was also used to calculate the restoration of contact surface area with stem subsidence for both a dual-taper and triple-taper geometry. A finite element analysis (FEA) was used to compare the effects of reduced contact area due to the incongruent hip implant-cement interface. Results: The contact model showed a large decrease in surface contact area with even only a small rotation going from 100% at 0° to 50.00% at 2.5° for the dual-taper geometry, and from 100% at 0° to 50.20% at 2.5° for the triple-taper geometry. There was a gradual but small ongoing decrease in contact surface with increasing rotation for both the dual-taper and triple-taper geometries. For both taper designs, there was an increase in contact surface area with an increase in subsidence resulting in contact for up to a 5° mismatch being restored with 2 mm subsidence. FEA showed that with increasing mismatches and consequent contact area reduction, there was an increase in von Mises stress in the implant-cement interface of up to 235%. Conclusion: With increasing mismatch, there was an increase in maximum stresses, total strain, and subsidence in the cement mantle, highlighting the importance of achieving an optimal implant-cement interface at the time of implantation of cemented PTF femoral stems. Cite this article: Bone Joint Res 2025;14(7):642–655.